Pleasing or Fighting Future Tastes? Projection Bias versus Conflict of Selves - Sebastian Krügel; Matthias Uhl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Previous studies apparently demonstrate that people systematically mispredict future tastes. This evidence, however, is also consistent with the idea that people understand, but do not approve of their future tastes. To disentangle both approaches, we conducted a framed field experiment with commitment option. In our experiment, commitment was a judgment which a planner imposed on another planner. The results suggest that people may sometimes experience a conflict between two far-sighted selves.
Keywords: D03; 330